2002
DOI: 10.1128/aac.46.11.3518-3521.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of 5-Fluorocytosine against 8,803 Clinical Isolates of Candida spp.: Global Assessment of Primary Resistance Using National Committee for Clinical Laboratory Standards Susceptibility Testing Methods

Abstract: MICs were determined by broth microdilution tests performed according to NCCLS guidelines by using RPMI 1640 as the test medium and the following interpretive breakpoints: susceptible (S), <4 g/ml; intermediate (I), 8 to 16 g/ml; resistant (R), >32 g/ml. 5FC was very active against the 8,803 Candida isolates (MIC 90 , 1 g/ml), 95% S. A total of 99 to 100% of C. glabrata (MIC 90 , 0.12 g/ml), C. parapsilosis (MIC 90 , 0.25 g/ml), C. dubliniensis (MIC 90 , 0.12 g/ml), C. guilliermondii (MIC 90 , 0.5 g/ml), and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
56
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 44 publications
6
56
1
3
Order By: Relevance
“…C. albicans was 10% and C. tropicalis was 33.3% resistant to Itraconazole which is comparable to other study which shows resistance of C. albicans ranging from 0-10% and C. tropicalis from 0-21.1%. 16,24,31 These findings suggest emergence of Itraconazole resistance C.tropicalis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…C. albicans was 10% and C. tropicalis was 33.3% resistant to Itraconazole which is comparable to other study which shows resistance of C. albicans ranging from 0-10% and C. tropicalis from 0-21.1%. 16,24,31 These findings suggest emergence of Itraconazole resistance C.tropicalis.…”
Section: Discussionmentioning
confidence: 78%
“…The result shows that the candida isolates were less resistance than other study which describe 0-3% resistance in C. albicans and 7-30% resistance in C.tropicalis. [31][32][33][34] CONCLUSION: Fungal infections and resistance to antifungal agents have been identified as an important problem. Extreme of ages, ICU stay, antimicrobial therapy, indwelling devices have been observed as important predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of 35% of C. tropicalis isolates resistant to 5FC is unusual (3). Other studies report between 0 (12) and 15% (13) with intermediate values (14)(15)(16), and all the isolates stored as C. tropicalis in the CBS collection since 1912 exhibited 5FC MIC <0.5 μg/mL.…”
Section: Discussionmentioning
confidence: 98%
“…Recent large scale studies, however, have revealed primary resistance of C. albicans to be in the range of 3.0 to 6.5% (2,14). It has recently been shown that intrinsic resistance to 5FC is associated with only one of the major clades of C. albicans (18).…”
Section: Discussionmentioning
confidence: 99%